Insights into catalysis and regulation of non-canonical ubiquitination and deubiquitination by bacterial deamidase effectors - Yong Wang (Nature Portfolio, 2020)
The bacterial effector MavC can ubiquitinate the host E2 enzyme UBE2N to dampen the host immune response. Here, the authors provide mechanistic insight into this non-canonical ubiquitination machinery and reveal the structural basis for the functional differences between MavC and its close homolog MvcA.